Alter Egos: Hillary Clinton, Barack Obama, and the Twilight Struggle Over American Power - Mark Landler (Random House, 2016)
n Alter Egos, veteran New York Times White House correspondent Mark Landler takes us inside the fraught and fascinating relationship between Barack Obama and Hillary Clinton—a relationship that has framed the nation’s great debates over war and peace for the past eight years.